2019
DOI: 10.1155/2019/2501039
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Electrospun Gelatin Nanofibers for Use as Nonaqueous Electrolyte in Electric Double-Layer Capacitor

Abstract: A novel nanofibrous gel electrolyte was prepared via gelatin electrospinning for use as a nonaqueous electrolyte in electric double-layer capacitors (EDLCs). An electrospinning technique with a 25 wt% gelatin solution was applied to produce gelatin electrospun (GES) nanofiber electrolytes. Structural analysis of the GES products showed a clearly nanofibrous structure with fiber diameters in the 306.2–428.4 nm range and exhibiting high thermal stability, high tensile strength, and a stable form of nanofibrous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Besides this, the mixture of solvents, for example, acetone/dimethylacetamide and chloroform/methanol have been employed for dissolving a cellulose derivative such as cellulose acetate [24][25][26]. On the other hand, PVA, starch, and gelatin can be dissolved in a polar solvent, such as water [33,34].…”
Section: Ionic Liquids As Additives For Preparing Electrospinning Sol...mentioning
confidence: 99%
See 3 more Smart Citations
“…Besides this, the mixture of solvents, for example, acetone/dimethylacetamide and chloroform/methanol have been employed for dissolving a cellulose derivative such as cellulose acetate [24][25][26]. On the other hand, PVA, starch, and gelatin can be dissolved in a polar solvent, such as water [33,34].…”
Section: Ionic Liquids As Additives For Preparing Electrospinning Sol...mentioning
confidence: 99%
“…The symbol '⇑' corresponds to an increase in the properties, and '⇓' corresponds to a decrease in the properties, while '⇕' and '-' describe unchanged and not available, respectively. [39]; and (c) electrospun gelatin fibers [33] assisted by different ionic liquids as additives. Figure 7.…”
Section: Properties Of Electrospun Biodegradable Polymer Fibers Assis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Gelatin nanofibers (like collagen) have been used in biomedical applications such as cosmetics, wound dressing, tissue engineering, surgical treatments, etc [34]. Gelatin nanofibers (having sufficient mechanical properties to be used in these applications as nanofibrous mats) have been electrospun for ultrathin nanofibers [34][35][36][37][38][39][40][41][42][43][44]. These authors also reported that the properties of these nanofibers can be tailored as per requirements by optimizing input parameters such as voltage, viscosity, distance between the spinneret and rotating drum collector, and flow rate.…”
Section: Introductionmentioning
confidence: 99%